THE EFFECT OF INTRINSIC MOTIVATION ON ENGLISH LANGUAGE LEARNING AMONG SECONDARY SCHOOL STUDENTS - Mimin Aminah; Muhammad Anjar Nugraha (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2021)
Abstract—In Pandemic situation students forced to deal with learning in 4.0 era. This era demanding student to be active in learning process. Thus, students’ factor, take control result of teaching learning beyond all kind of learning model that was presented in any research. Intrinsic motivation is one of many factors that can impact on success or failure for a complex challenge. With high motivation students could looking for many ways to get their goals. It is very affected when students have good motivation to study English as a new skill for them. In Indonesia exclusively, English is a foreign language. In a public senior high school mostly English just 4 hours per-weeks and it is less than enough to improve Students English skill, so here motivation take important part to make sure they could find another way to improve their English Skill in the condition that could not support their needs. Therefore, the purpose of this research to investigate how effective intrinsic motivation on English language learning among secondary school students. The data were collected through observational field notes, questionnaire and test of English competency. The researcher expected this research can give overview about students’ language learning process and outcomes.